Is there a role for the funeral service provider in bereavement support within the context of compassionate communities?. Issue 10 (26th November 2019) - Aoun, Samar M.; Lowe, Jennifer; Christian, Kim M.; Rumbold, Bruce
Abstract: This is the first study to explore bereaved individuals' experiences of funeral service providers using these services' databases. A total of 839 Australians participated in a postal survey, 6–24 months into their bereavement. Funeral providers were reported to be the third most prevalent form of bereavement support after friends and family. Analysis found six themes related to perceived helpful or unhelpful support: instrumental support, professionalism, informational support, financial tension, communication, and emotional support. Funeral providers could improve their support by adopting a proactive approach to bereavement needs and offering personalized and ongoing support. We develop these suggestions by exploring their potential contributions to building community capacity around death, dying and bereavement.